The Effect of Professional Skepticism, Experience of Investigative Auditors and Whistleblowing System on Auditor's Ability in Detecting Fraud - Pamela Citranagari, Monica (Publikasi Indonesia, 2022)
This study aims to determine the effect of professional skepticism, auditor experience, and whistleblowing system on the auditor's ability to detect fraud. There are 2 problems that often occur in accounting, namely due to human error and then due to intentional errors. Errors and fraud have differences that lead to errors in a financial statement. Referring to various cases both at home and abroad, it shows that fraud can happen anywhere. For this reason, efforts to prevent and eradicate fraud need to be improved and intensified. The way the government handles and uncovers fraud that occurs, one of which is by conducting an investigative audit, and the public's concern for reporting on the whistleblowing system is also very effective in revealing corruption and fraud that occurred. The population in this study were all private internal and external auditors (Public Accounting Firms). Data collection techniques in this study using a questionnaire. This type of research is a hypothesis testing research. The number of samples collected is 56 respondents. The sampling technique used is convenience sampling. The results of this study indicate that: 1) Professional Skepticism has a positive effect on the auditor's ability to detect fraud. 2) The experience of the investigative auditor has a positive effect on the auditor's ability to detect fraud. 3) The whistleblowing system has a positive effect on the auditor's ability to detect fraud.